The Relationship Between Information Sources and the Attitudes of Breastfeeding Mothers in the Success of Exclusive Breastfeeding at PMB Bdn. Tri Utami Sari, S.SiT - Umi Khasanah; Hasna Try Aryani; Fitriani Nur Damayanti (Universitas Muhammadiyah Semarang, 2026)
Background: Exclusive breastfeeding is an important factor in maternal and infant health, but its success rate in Indonesia, including in Semarang, is still low. One of the factors that influences the success of exclusive breastfeeding is the source of information and the attitude of breastfeeding mothers. Purpose: To analyze the relationship between information sources and the attitudes of breastfeeding mothers in the success of exclusive breastfeeding at PMB Bdn. Tri Utami Sari, S.SiT using a quantitative research approach. Method: A quantitative study with a cross-sectional design was conducted on 51 breastfeeding mothers at PMB Bdn. Tri Utami Sari, S.SiT. Data were collected through questionnaires to identify information sources and maternal attitudes, analyzed using the Spearman Rho test. Result: The majority of mothers (82.4%) exhibited a positive attitude toward exclusive breastfeeding, with the primary information source being healthcare providers (23.5%). Statistical analysis revealed a moderate positive correlation (r = 0.388) that was statistically significant (p = 0.005) between information sources and maternal attitudes. Healthcare providers and mass media supported positive attitudes, while family influence tended to correlate with negative attitudes. Conclusion: There is a significant relationship between information sources and the attitudes of breastfeeding mothers, where information from healthcare providers enhances positive attitudes toward the success of exclusive breastfeeding.